Radon isotopes as tracers of climate-sensitive subsurface connectivity in Antarctic permafrost - L. Ruggiero; A. Sciarra; A. Mazzini; F. Florindo; G. Wilson; C. Mazzoli; P. Tuccimei; G. Galli; L. Tositti; A. Zappi; J. Anderson; L. Davidson; et al. (Environmental Research, 2026)

Impact of Terrestrial Weather on the Space Weather of the Ionosphere-Thermosphere: Initial Results from a NASA Living with a Star Focused Science Topic - J. Oberheide; D. Aggarwal; B. Bergsson; S. Chakraborty; S. Debchoudhury; M. Dhadly; F. Gasperini; L. Goncharenko; V. L. Harvey; C. Heale; P. Inchin; J. Li; et al. (Surveys in Geophysics, 2025)
The ionosphere-thermosphere (IT) is a convergence point of energy and processes that interconnect Earth’s atmosphere with space. Processes generated by terrestrial weather in the lower atmosphere (i.e., troposphere and stratosphere, altitudes less than ~ 50 km) are recognized by the scientific community as sources of variability in both the structure and composition of the IT. Exposed to persistent wave forcing from terrestrial weather sources and solar and magnetic forcing, the IT is a domain of compelling scientific inquiry that connects thermodynamics, fluid dynamics, electrodynamics and plasma physics. Predicting its space weather is of significant national interest for space situation awareness including the very low earth orbit as the new frontier of space operations. Advancing the understanding of whole atmosphere interconnections between terrestrial and space weather requires coordinated modeling and observational efforts across different spatial and temporal scales. Toward this goal, the National Aeronautics and Space Administration (NASA), through the living with a star (LWS) program, established in 2022 a focused science topic (FST) to study the problem from various angles. In this manuscript we report on the vision, goals and status of the ongoing FST “Impact of Terrestrial Weather on the Ionosphere—Thermosphere”. Initial results show bigger impacts on the IT than hitherto thought and help to more clearly define the state-of-the-art in the context of future NASA missions such as EZIE, DYNAMIC and GDC.

Surprising concentrations of hydrogen and non-geological methane and carbon dioxide in the soil - G. Etiope; G. Ciotoli; E. Benà; C. Mazzoli; T. Röckmann; M. Sivan; A. Squartini; T. Laemmel; S. Szidat; N. Haghipour; R. Sassi (Science of The Total Environment, 2024)

Antarctic permafrost degassing in Taylor Valley by extensive soil gas investigation - L. Ruggiero; A. Sciarra; A. Mazzini; F. Florindo; G. Wilson; M.C. Tartarello; C. Mazzoli; J.T.H. Anderson; V. Romano; R. Worthington; S. Bigi; R. Sassi; et al. (Science of The Total Environment, 2023)

The addition of entropy-based regularity parameters improves sleep stage classification based on heart rate variability - M. Aktaruzzaman; M. Migliorini; M. Tenhunen; S. L. Himanen; A. M. Bianchi; R. Sassi (Medical & Biological Engineering & Computing, 2015)

The dimensionality of ecological networks - Anna Eklöf; Ute Jacob; Jason Kopp; Jordi Bosch; Rocío Castro‐Urgal; Natacha P. Chacoff; Bo Dalsgaard; Claudio de Sassi; Mauro Galetti; Paulo R. Guimarães; Silvia Beatriz Lomáscolo; Ana M. Martín González; et al. (Ecology Letters, 2013)
How many dimensions (trait‐axes) are required to predict whether two species interact? This unanswered question originated with the idea of ecological niches, and yet bears relevance today for understanding what determines network structure. Here, we analyse a set of 200 ecological networks, including food webs, antagonistic and mutualistic networks, and find that the number of dimensions needed to completely explain all interactions is small (

Targeted Delivery of PSC-RANTES for HIV-1 Prevention using Biodegradable Nanoparticles - Anthony S. Ham; Marilyn R. Cost; Alexandra B. Sassi; Charlene S. Dezzutti; Lisa Cencia Rohan (Pharmaceutical Research, 2009)

Structural details and composition of Trichomonas vaginalis lipophosphoglycan in relevance to the epithelial immune function - Bibhuti N. Singh; Gary R. Hayes; John J. Lucas; Ulf Sommer; Nelly Viseux; Ekaterina Mirgorodskaya; Radiana T. Trifonova; Rosaria Rita S. Sassi; Catherine E. Costello; Raina N. Fichorova (Glycoconjugate Journal, 2009)

POTOS: a portable topographic system for measuring inaccessible muddy creek areas - Darío R. Minkoff; Gerardo M. E. Perillo; Daniel E. Perez; Silvio D. Maraschín; Maximiliano Sassi (Wetlands Ecology and Management, 2007)

Trace element distribution in Central Dabie eclogites - R. Sassi; B. Harte; D. A. Carswell; H. Yujing (Contributions to Mineralogy and Petrology, 2000)